(untitled) (Proceedings of the International Conference on Future of Education, 2018)
This study was aimed to identify challenges and barriers to implement ESD in Secondary Schools in Sri Lanka. The samples were 36 Geography teachers from 36 1AB & 1C schools out of 54 schools. Samples were selected from the Kandy district and stratified random sampling method was used. Objectives were to identify challenges and barriers related to ESD in school curriculum, to investigate the challenges and barriers related to teachers in teaching ESD, to suggest ways and means to face the challenges and barriers. Data was collected by the survey method and the quantitative and qualitative data collected. Analysis was done descriptively. Challenges and barriers identified were; not including ESD as a core topic in the school curriculum, exam oriented mentality of students, lack of awareness of Sustainable Development (SD) and ESD concepts among teachers, lack of ESD programmes in the school time table, lack of funds, time and resource persons to carry out ESD programmes. The study recommended that curriculum enhancement and implementation of programmes to create awareness of SD and ESD with the concepts originated from the range of themes selected from the syllabi from Grade 6 to 13, a specialized SD and ESD teacher training, converting teachers to be change agents with a broad vision towards 17 SD Goals 2030 and identifying strengths and opportunities to implement ESD in the school programmes.